2007
DOI: 10.1088/1748-9326/2/4/045025
|View full text |Cite
|
Sign up to set email alerts
|

Linking requirements with capabilities for deforestation monitoring in the context of the UNFCCC-REDD process

Abstract: As the United Nations Framework Convention on Climate Change nears the end of a two-year period of evaluation of the issue of reducing emissions from deforestation in developing countries, participating countries have agreed on the need to address this globally important source of greenhouse gas emissions. Negotiations on policy frameworks to monitor and reduce deforestation rely on an understanding of the scientific and technical capacity to support these efforts. Current UNFCCC programs to improve observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 13 publications
1
63
0
3
Order By: Relevance
“…In addition to being timely and cost effective [18], satellite based monitoring enables a transparent and reliable [19] means to monitor forest cover conditions. Although errors in the interpretation of spectral response and human bias exist [20,21], remote sensing remains to play key role in identifying and estimating deforested and reforested areas [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being timely and cost effective [18], satellite based monitoring enables a transparent and reliable [19] means to monitor forest cover conditions. Although errors in the interpretation of spectral response and human bias exist [20,21], remote sensing remains to play key role in identifying and estimating deforested and reforested areas [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed approaches to the use of tree models will have to take the following into consideration: (1) data availability (raw data, metadata, models, and forest inventory data), (2) the biophysical and environmental context, and (3) the human, financial, and technical capabilities (Herold and Johns 2007), i.e., some countries do not have university courses in the field of forestry or do not have funds allocated to ensure data collection, storage, and management. Raw data are needed to allow the validation of the estimates and perform accuracy assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers Grainger and Obersteiner, 2011;Herold, 2009;Herold and Johns, 2007;Palmer Fry, 2011;Pratihast et al, 2013;Romijn et al, 2012;Skutsch and McCall, 2010) have examined the technical capacity of REDD+ countries to monitor REDD+ impacts. These researchers have concluded that most REDD+ countries not only have low technical capacity but also weak institutional capacity to monitor REDD+ impacts.…”
Section: Scholarship On Forest Monitoring For Redd+ and Emerging Resementioning
confidence: 99%
“…This is so because in most scholarly debates (e.g. Asner et al, 2009;GOFC-GOLD, 2013;Hansen et al, 2013;Hansen et al, 2008;Herold, 2009;Herold and Johns, 2007;Romijn et al, 2012; forest monitoring for REDD+ is considered a highly technical, value-free and apolitical activity. However, building on the work of others Kowler and Larson, 2016;Vijge, 2016;Visseren-Hamakers et al, 2012), this dissertation argues that the concept of forest monitoring, and MRV in particular, is largely political.…”
Section: Scholarship On Forest Monitoring For Redd+ and Emerging Resementioning
confidence: 99%
See 1 more Smart Citation